Answer:
p = -4
Explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:
5*p-2*p-(-12)=0
Step 1 :
Pulling out like terms :
1.1 Pull out like factors :
3p + 12 = 3 • (p + 4)
Step 2 :
Equations which are never true :
2.1 Solve : 3 = 0
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
2.2 Solve : p+4 = 0
Subtract 4 from both sides of the equation :
p = -4
One solution was found :
p = -4
Also to check the work:
5x-4=-20
2x-4=-8
-20 - -8= -12